P202 Are Chinese immigrants with CVD ready to use web-based health information: a comparative study in Australia. (13th January 2020) - Zhang, L; Ding, D; Gallagher, R
Abstract: Background: Immigrant populations often have poor access to cardiovascular disease (CVD) secondary prevention due to linguistic and cultural barriers. Web-based interventions are effective in risk reduction and lifestyle modification and may reach those hard-to-reach populations such as Chinese immigrants. However, less is known about the current use of web-based health information and confidence in use. Purposes: We compared the use of web-based health information and confidence in use between Chinese immigrants with CVD to those with and without another chronic condition; and explored the factors associated with the confidence in utilization. Methods: Chinese immigrants with CVD, musculoskeletal conditions, or no chronic condition were recruited from Chinese communities across New South Wales, Australia. E-health literacy scale was used to explore the perceptions of web-based health information and confidence in use. Demographic, clinical data and use of web-based health information were collected and health literacy was measured using a validated single screening question. Results: Participants (n = 90 CVD, n = 87 musculoskeletal, n = 154 no chronic conditions) were aged mean 59 ± 16 years, mostly female (69%), 75% reported fair to poor English proficiency, and 51% had completed university. The most accessed web-based health information concerned lifestyle (60%), health resources (45%), diseases (35%), and medications (30%). More than half (54%) were confident in using web-based health information. Participants with CVD were the oldest (71 vs 65 vs 49 years, p<.001) and participants with any chronic condition had less education (p<.001) and English proficiency (p<.001) than the healthy group. Approximately half of the participants with CVD perceived web-based health information as useful (48%) and important (46%), and the most accessed information concerned lifestyle and medication (56% and 32%). Participants with CVD accessed medication information more often than musculoskeletal group (32% vs 23%), but there was no difference in accessing other information. Both chronic groups showed no difference in accessing web-based medication and lifestyle information compared with the healthy group. Confidence in using web-based health information was similar for CVD and musculoskeletal groups and lower than the healthy group (p<.001). Participants with the least confidence to use web-based health information were older (p=.016), female (p=.014), had less than university level education (p<.001), and lower health literacy (p=.001) after adjusting for age, gender, education, English proficiency, employment status, social support, health literacy, and number of chronic conditions. Conclusions There is a strong potential to provide web-based medication and lifestyle information for Chinese immigrants with CVD if support is provided to improve confidence in this technology for older, women, and those with less education and/or health literacy.